Polydisperse stickiness and particle size on light scattering in dense colloidal suspensions: A numerical study using the binary sticky hard-sphere model - Hiroyuki Fujii; Koyata Nishikawa; Hyeonwoo Na; Kazumichi Kobayashi; Masao Watanabe (Results in Physics)
In nanotechnology using scattered light and colloidal science, it is crucial to model the agglomeration of submicrometer-scale particles and light scattering in dense colloidal suspensions and clarify the quantitative relation between them. We numerically examined the effects of polydisperse stickiness and particle sizes on the scattering properties in the near-infrared optical wavelength using the dependent scattering theory (one of the electromagnetic theory) and bidisperse (binary) sticky hard-sphere (SHS) model at different stickiness parameters and particle sizes. The SHS model has been widely employed as a particle interaction model, but most previous works are for a monodisperse system. Actual suspensions are polydisperse, and our simple bidisperse models allow us to provide a physical interpretation of the two polydisperse effects. We showed that polydisperse stickiness contributions are effectively reduced to monodisperse cases with a mean value of the stickiness parameters. Meanwhile, we showed strong effects of the polydisperse particle size, and its contribution is not reduced to a monodisperse case. At a small particle size (around 100 nm), the polydispersity effects enhance the scattering properties even in the diffusive region of radiative transfer.